Participation in planning – A study of urban development in Norway - Eva Irene Falleth (Politecnico di Torino, 2011)
In Norway, the dominance of neo-liberal ideas has resulted in a private planning practice whereby the developer is the principal actor in opaque negotiations between planning authorities and developers. We examine patterns of contact between stakeholders in urban development planning. Based on information obtained from a survey of the 145 most populous municipalities in Norway, as well as from case studies in Oslo, Bergen and Trondheim, we find considerable interaction between the stakeholders involved in the planning process. The interaction patterns are different for civil society actors and private developers. We find that while developers have contacts with the planning authorities, the civil actors have contacts with the politicians. In the initial phase, i.e. before formal planning begins, this pattern is highly significant. Politicians frequently feel bound by negotiations and agreements that are made by the planners and the developers during the initial planning process.